EXPLORING INTERRALTIONSHIPS BETWEEN INDIVIDUAL AND SOCIAL SUPPORT DOMAINS ON HEALTH CARE TRANSITION READINESS OF EMERGING ADULTS WITH CONGENITAL HEART DISEASE - Mayo, Margaret A. (East Carolina University, 2016)
Emerging adults with congenital heart disease or heart disease acquired during childhood (YACHD) require interdisciplinary services to facilitate their transition from pediatric to adult health care due to multiple components involved in the transition process. Adolescents with CHD face psychosocial challenges such low self-esteem and lack of peer support, which could potentially affect their health care transition (HCT). Summer camps can provide therapeutic benefits. Using an online, cross-sectional survey, the current descriptive study explored the experiences of 79 YACHD, 18-29 years old regarding self-esteem, friendships, medical specialty camp attendance and their reported transition readiness to adult health care. There was a statistically significant difference between YACHDs living with parents and those who have moved away from parental residence. Females scored higher than males on friendship closeness, self-esteem, and transition readiness. Participants reported gaining cognitive and social skills as well as developing friendships during camping experiences. These competencies have been identified in HCT literature as potentially useful for successful HCT outcomes. Recommendations are made for recognizing and exploring medical specialty camping environment as a social support resource for its potential in providing developmentally supportive HCT related education.
Keywords: emerging adulthood; camp; social support; health care transition; Interpersonal relations in young adults; Young adults--Health aspects; Congenital heart disease; Self-esteem in young adults